Assessment of readiness for launching cloud computing services: The case of Ethio‐Telecom in Ethiopia. Issue 4 (17th January 2022) - Mengesha, Getachew H.; Musa, Philip F.; Negash, Solomon; Leuleged, Ruth; Munchus, George
Abstract: A nation's telecom system plays an important role in its socio‐economic development. This case study assesses the technical and organizational readiness of Ethio‐Telecom to implement Cloud Computing services to serve Africa's fast‐growing demand for Cloud Computing. The study used the STOPE (Strategy, Technology, Organization, People, and Environment) model as a theoretical base. A structured survey questionnaire was used to gather data from 100 mid and operational level employees. An interview was conducted with top‐level officials to elicit information about the strategic direction of the company. We used structural equation modeling software for analyses and model testing. The SMART PLS results point to the appropriateness of the STOPE model for the assessment of Ethio‐Telecom's Cloud Computing readiness. Additional analysis revealed that Ethio‐Telecom's Strategy, Technology, Organization, and Environmental dimensions need only minor improvements while the People dimension requires significant improvements to successfully implement Cloud Computing services. We mapped interview and document analysis data to the STOPE model constructs. This qualitative approach further validated the results we got in the quantitative analysis. We believe the mixed methodology, SMART PLS for quantitative analysis and e‐Learning Readiness Survey to determine individual dimension readiness, and quantitative analysis, used in this study have added to the body of knowledge.